2021
DOI: 10.2147/rmhp.s318858
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Food System Topics from the Consumers’ Perspective in a Developing Country Context: Key Insights from ANRS Metropolitan Cities, Ethiopia

Abstract: Background: The food system is an interdisciplinary global issue with substantial social and economic challenges. These challenges are most pronounced in developing countries, where chronic under-nutrition is prevalent. The long-standing notion has been to solve malnutrition and undernutrition primarily from the supply side through improving productivity and production. Nevertheless, addressing the nutrition paradox requires understanding consumers' food choices and its drivers. Methods: This study forms a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Similarly, studies conducted in Uganda (90) and Nigeria (91) have shown a positive relationship between women's educational attainment and effective care for their children. Similar thoughts can be found in ( 51) and (52). It is known that knowledge empowers women, enabling them to change both their own lives and their children's lives for the better.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly, studies conducted in Uganda (90) and Nigeria (91) have shown a positive relationship between women's educational attainment and effective care for their children. Similar thoughts can be found in ( 51) and (52). It is known that knowledge empowers women, enabling them to change both their own lives and their children's lives for the better.…”
Section: Discussionsupporting
confidence: 64%
“…As shown in Figure 1, having more bargaining power enables women to negotiate for access to resources for themselves and their children, which in turn helps improve their children's nutrition outcomes, as argued in (48,49). Malnutrition and women's disempowerment still remain signi cant challenges in developing countries like Ethiopia (50,51,52). According to the Ethiopian Mini Demographic and Health Survey 2019 report, the prevalence of stunting and wasting are among the highest in the world (50).…”
mentioning
confidence: 99%